Analisis Persepsi Kemudahan Dan Persepsi Manfaat Terhadap Niat Menggunakan Social Commerce (Studi Kasus Pada Ukm Di Kabupaten Magetan) - Firdha Afsari Putri; Yessy Artanti; Sri Setyo Iriani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Along with the rapid development of technology, the digital world and the internet have an impact on the world of marketing. Global marketing trends are shifting from traditional or conventional to digital or online. Some online marketing tools that SME actors can consider are social media. Social media that can be used include Instagram, Facebook, and Tiktok. The following research aims to analyze the effect of perceived ease of use and perceived usefulness on intention to use. The following research uses a quantitative type of study. Respondents in this research are SME actors in Magetan Regency who have used social media but have never marketed their products through social commerce with aged over 17 years. The data obtained from 100 subjects were processed using multiple linear regression analysis technique. The research results explain that perceived ease of use has positive effect on intention to use and perceived usefulness have a positive effect on intention to use.